Stress-relieving plant growth-promoting bacterial co-inoculation enhances nodulation and nitrogen uptake in black gram under nitrogen-free saline conditions - Tiwari, Praveen Kumar; Srivastava, Anchal Kumar; Singh, Rachana; Srivastava, Alok Kumar (Frontiers in Microbiology, 2025)
Non-halophytic plants are highly susceptible to salt stress, but numerous studies have shown that halo-tolerant microorganisms can alleviate this stress by producing phytohormones and enhancing nutrient availability. This study aimed to identify and evaluate native microbial communities from salt-affected regions to boost black gram (Vigna mungo) resilience against salinity, while improving plant growth, nitrogen uptake, and nodulation in saline environments. Six soil samples were collected from a salt-affected region in eastern Uttar Pradesh, revealing high electrical conductivity (EC) and pH, along with low nutrient availability. A total of 72 bacterial strains were isolated from soil and 28 from black gram (Vigna mungo) root nodules, with 32 of the soil bacteria tolerating up to 10% NaCl. These bacteria were characterized through taxonomic and biochemical tests. Cross-compatibility analysis showed two rhizobia strains were highly compatible with five salt-tolerant bacteria. These strains exhibited significant plant growth-promoting traits, including phosphate, potassium, and zinc solubilization, as well as ACC deaminase, IAA, siderophore, and EPS production. Strain Paenibacillus sp. SPR11 showed the strongest overall performance. Genetic diversity was assessed using BOX-PCR and ERIC-PCR, and strains were identified through 16S rRNA gene sequencing. In a seed germination study under saline conditions (200 mM and 300 mM), co-inoculation with Bradyrhizobium yuanmingense PR3 and Paenibacillus sp. SPR11 resulted in a significant enhancement in seed germination (40%), root growth (84.45%), and shoot growth (90.15%) compared to single inoculation of B. yuanmingense PR3. Under greenhouse conditions in Leonard jars, co-inoculation with strains PR3 and SPR11 significantly enhanced shoot and root length, fresh and dry biomass, nodule count, and nodule fresh and dry weight. Chlorophyll content, nutrient uptake, and crude protein levels increased, while proline content decreased compared to single inoculation and uninoculated seeds. Our best understanding leads us to believe that this is the very first report of utilizing co-inoculation of salt-tolerant Paenibacillus sp. SPR11 and B. yuanmingense PR3, demonstrating their promising potential to alleviate salt stress and enhance growth, root architecture, nitrogen uptake, and nodule formation in black gram under nitrogen free saline conditions.